Energy Consumption Optimization in Commercial Buildings Using IoT-Based Monitoring - Wicaksono, Dimas Arif; Rahman, Nur Aisyah; Ferreira, Lucas M. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Energy consumption in commercial buildings continues to rise due to increased demand for comfort, automation, and operational continuity. Conventional energy management systems often fail to provide adaptive, real-time control, resulting in inefficiencies and unnecessary energy waste. This study examines the role of Internet of Things based monitoring systems in optimizing energy consumption within commercial buildings. The research adopts a systematic analytical approach by synthesizing empirical findings from recent IoT-based energy management studies and integrating them into a unified monitoring and control framework. The analysis focuses on occupancy detection, environmental sensing, data-driven control, and predictive analytics. Results indicate that IoT-based monitoring enables energy reductions ranging from 11 percent to over 30 percent, particularly in HVAC and lighting systems. Real-time data acquisition and automated control significantly improve operational efficiency while maintaining occupant comfort. The findings confirm that IoT-based monitoring systems provide measurable energy savings, enhance decision accuracy, and support sustainable building operations. This study contributes a structured evaluation of IoT-driven energy optimization strategies and offers practical insights for commercial building managers and policymakers seeking scalable and cost-effective energy solutions.